The Reform of the German Works Constitution Act: A Critical Assessment - Addison, John T.; Bellmann, Lutz; Schnabel, Claus; Wagner, Joachim (Industrial relations, 2004)
Since 1920, the thrust of German law on workplace codetermination has changed on a number of occasions. We describe the latest swing of the legislative pendulum-favoring works council formation and competence-and evaluate the case for it. We provide new information on the extent of works councils before reviewing the evidence on their economic effects, focusing on some new results from matched-plant data. If the former evidence points to a codetermination deficit, this shortfall does not appear to have negative consequences for workplace productivity, profitability, and employment. © 2004 Regents of the University of Californi
UnivIS-Import:2015-03-09:Pub.2004.rw.fbwiwi.theref